The use of social networking sites (facebook) and its impact on social relations (Journal Of Educational and Psychological Researches, 2016)
Is the subject of Facebook of more topics that aroused interest and that it provides the features and services that allows users to direct communication and interaction and dialogue with others, and deals with the subject of research the use of Facebook and its effects left by the social relations, as the field study was conducted on a sample of 130 students from students Baghdad University of males and females in the Faculty of Political Science and Agriculture, Science and Education, Girls, and limited the sample to Facebook users exclusively to test the study hypotheses and relationships connectivity, and the results revealed the presence of a significant impact of Facebook in the social relations of users and keeping their distance from reality and spend long times in front of the means by which to deal with Facebook leaving positive and negative effects on users.